Effects of high temperature after pollination on physicochemical properties of waxy maize flour during grain development. (28th October 2013) - Lu, Dalei; Cai, Xuemei; Yan, Fabao; Sun, Xuli; Wang, Xin; Lu, Weiping
Abstract BACKGROUND Waxy maize is grown in South China, where high temperatures frequently prevail. The effect of high‐temperature stress on grain development of waxy maize is not known. RESULTS High temperature decreased the grain fresh weight and volume, and lowered the grain dry weight and water content after 22 days after pollination (DAP). Plants exposed to high temperature had low starch content, and high protein and soluble sugar contents at maturity. Starch iodine binding capacity and granule size were increased by heat stress at all grain‐filling stages. The former parameter decreased, while the latter parameter increased gradually with grain development. High temperature increased the peak and breakdown viscosity before 30 DAP, but the value decreased at maturity. Pasting and gelatinization temperatures at different stages were increased by heat stress and gradually decreased with grain development under both high‐temperature and control conditions. Gelatinization enthalpy increased initially but decreased after peaking at 22 DAP under both control and heat stress conditions. High temperature decreased gelatinization enthalpy after 10 DAP. Retrogradation percentage value increased with high temperature throughout grain development. CONCLUSION High temperature after pollination changes the dynamics of grain filling of waxy maize, which may underlie the observed changes in its pasting and thermal properties. © 2013 Society of Chemical Industry